MoO3 with the Synergistic Effect of Sulfur Doping and Oxygen Vacancies: The Influence of S Doping on the Structure, Morphology, and Optoelectronic Properties - Jian Yu; Zhaokang Zheng; Aiwu Wang; Muhammad Humayun; Yasser A. Attia (Nanomaterials, 2024)
Molybdenum trioxide (MoO3) is an attractive semiconductor. Thus, bandgap engineering toward photoelectronic applications is appealing yet not well studied. Here, we report the incorporation of sulfur atoms into MoO3, using sulfur powder as a source of sulfur, via a self-developed hydrothermal synthesis approach. The formation of Mo-S bonds in the MoO3 material with the synergistic effect of sulfur doping and oxygen vacancies (designated as S-MoO3−x) is confirmed using Fourier-transform infrared (FTIR) spectroscopy, X-ray photoelectron spectroscopy (XPS), and electron paramagnetic resonance (EPR). The bandgap is tuned from 2.68 eV to 2.57 eV upon sulfur doping, as confirmed by UV-VIS DRS spectra. Some MoS2 phase is identified with sulfur doping by referring to the photoluminescence (PL) spectra and electrochemical impedance spectroscopy (EIS), allowing significantly improved charge carrier separation and electron transfer efficiency. Therefore, the as-prepared S-MoO3−x delivers a sensitive photocurrent response and splendid cycling stability. This study on the synergistic effect of sulfur doping and oxygen vacancies provides key insights into the impact of doping strategies on MoO3 performance, paving new pathways for its optimization and development in relevant fields.